Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s11664-004-0184-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spin coating on the curing rate of epoxy adhesive for the fabrication of a polymer optical waveguide

Abstract: Spin coating is a simple process for rapidly depositing thin, solid polymeric films onto relatively flat substrates. Evaporation occurs during spinning of the relatively volatile species in any solution. The curing behavior of spin-coated polymeric film is influenced by the evaporation of any reactive component. An investigation was carried out on a silicon substrate to study the effects of spin coating on the curing behavior of the epoxy adhesive. The degree of curing for both spin and without spin-coated epo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…The slower reaction rate is due mainly to the material properties changing during spinning. 3 In another study, the lower thermal and chemical stabilities for spin-coated adhesive were also observed due to rapid fluid flow and convectively driven evaporation that occur during spinning. It was also lower at the border side of the spincoated polymer layer due to the spinning force experienced there being highest, the greater number of voids, and the low cross-link density.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The slower reaction rate is due mainly to the material properties changing during spinning. 3 In another study, the lower thermal and chemical stabilities for spin-coated adhesive were also observed due to rapid fluid flow and convectively driven evaporation that occur during spinning. It was also lower at the border side of the spincoated polymer layer due to the spinning force experienced there being highest, the greater number of voids, and the low cross-link density.…”
Section: Discussionmentioning
confidence: 94%
“…Throughout this investigation, 2 cm 3 2 cm square edge silicon wafers were used to avoid the radial nonsymmetry in rectangular substrates that causes larger corner build-up effects on spincoated polymer films. 3 After standard cleaning, sample types 3-5 were plasma-etched with sulfur hexafluoride (SF 6 ) and the oxygen mixture (SF 6 1 O 2 ) of process gas. The etching was done in a reactive ion-etching plasma chamber (PlasmaTherm 790 Series).…”
Section: Substrate Cleaning and Surface Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Volatile solvent evaporates during spinning in any solution. It is the most common technique of coating thin films onto wafers because of that it makes uniform films with well-controlled thickness [20].…”
Section: Introductionmentioning
confidence: 99%